Mn3O4 nanoparticles encapsulated in carbon cages as the electrode of dual-mechanism supercapacitors. (June 2019) - Paredes Camacho, R.A.; Wu, A.-M.; Gao, S.; Jin, X.-Z.; Cao, G.-Z.; Huang, H.
Abstract: This article reports the production of Mn3 O4 @C nanocomposites as electrodes for high-performance supercapacitor applications. A facile and low-cost synthesis method combining DC arc discharge and annealing in air at different temperatures is used. The influence of the oxidation temperatures on product microstructure and electrochemical performance is studied in detail. The Mn3 O4 @C nanocomposite obtained under 200 °C annealing owns the highest specific capacitance of 422 Fg -1, with a specific energy density of 36 Whkg −1 and excellent stability after 1000 cycles. The enhanced electrochemical response is attributed to a well-defined core-shell structure that has a defect-enriched carbon shell and pseudocapacitive Mn3 O4 core. Carbon promotes the ion exchange with electric double-layer capacitance, while Mn3 O4 contributes the pseudocapacitance during its faradaic redox reactions. Highlights: Plasma evaporation and thermal oxidation are used to produce Mn3 O4 @C nanocages. The optimum oxidation temperature that preserves the core-shell structure is 200 ⁰C. Mn3 O4 @C delivered excellent capacitance of 422 Fg -1 and high stability after 1000 cycles. Outstanding electrochemical performance is endorsed to a dual-mechanism of energy storage.